Hubungan Ketangguhan Mental dengan Kecemasan Bertanding pada Atlet Puslatcab Pencak Silat di Ponorogo - Ardhi Nur Wahid; Pudjijuniarto Pudjijuniarto; Made Pramono; Himawan Wismanadi (Pusat Riset dan Inovasi Nasional, 2025)
Psychological resilience plays a vital role in supporting athletes in overcoming anxiety that arises during competition. The purpose of this study was to assess the relationship between psychological resilience and anxiety during competition, and the extent to which psychological resilience affects the level of anxiety. The correlational method was applied in this study with a purposive sampling technique, involving 30 athletes from the Pencak Silat Training Center in Ponorogo as participants. Data were collected through a questionnaire that measured the scale of psychological resilience and competition anxiety. Data analysis using the product moment correlation test revealed a negative relationship with a correlation coefficient of -0.571 (r = -0.571). This finding indicates that the higher the psychological resilience, the lower the level of anxiety felt during competition. In addition, the results of the determination coefficient analysis showed that psychological resilience contributed 32.6% to the level of competition anxiety, while the remaining 67.4% was influenced by other variables not discussed in this study.